Early Screening of Chronic Kidney Disease (CKD) Among the Patients of Punjab, Pakistan - Farooq, Bakhtawar; Munfoosa Jaffar; Zahid Habib Qureshi; Mehwish Iqbal; Muhammad Faisal; Muhammad Tahir Khan; Madeeha Shahzad Lodhi (Journal of Liaquat University of Medical & Health Sciences, 2026)
OBJECTIVE: To explore the early detection of chronic kidney disease (CKD) through primary care physicians (PCPs) and laboratory testing. METHODOLOGY: A case-control study involving 200 participants with diabetes, hypertension, cardiovascular disease, arthritis, and chronic glomerulonephritis was conducted at Nishtar and Ibn-e-Sina Hospital, Multan, Pakistan, from November 2023 to May 2024. Participants’ medical histories were documented, creatinine was measured by the rate-Jaffe method, and estimated glomerular filtration rate (eGFR) was calculated using the Modification of Diet in Renal Disease (MDRD) equation. Laboratory tests were carried out. Statistical analysis was performed using one-way ANOVA via the computer software GraphPad Prism. RESULTS: Of 200 participants, 113 were identified as CKD patients, 17 as acute kidney injury (AKI), and 70 as healthy controls. The eGFR values were significantly reduced in AKI (5.53mL/min/1.73 m² ± 2.71) and CKD (17.9mL/min/1.73 m² ± 15.5) patients, and the creatinine levels increased dramatically in AKI (11.69mg/dl ± 4.71) and CKD (7.46 mg/dl ± 4.54) patients compared to their controls. Hemoglobin and platelets were decreased in CKD and AKI patients, while the total leukocyte count range increased in AKI patients, compared to controls. ESR was significantly increased in patients with CKD (49mm/hr ± 14.9) and AKI (65mm/hr ± 13) compared with the control group. The range of lymphocytes is decreased in CKD patients compared to controls. CONCLUSION: The study underscores the importance of PCPs and laboratory tests aligning with Kidney Disease: Improving Global Outcomes (KDIGO) guidelines for early and timely detection of CKD.